Предмет: Математика,
автор: ver88
Помогите пожалуйста!
буду очень благодарна!!!
упростите по формулам. хотя бы пару!((
Приложения:
![](https://files.topotvet.com/i/745/7456211fed0c6b962351276f965e33ae.jpg)
Ответы
Автор ответа:
0
1)18а-+(а-9)^2=18а + а^2 - 18а + 81= а^2 +81
2) (5х-1)^2- 25х^2= 25х^2 -10х +1 - 25х^2 = 1- 10х
3) 4х^2 - (2х-3)^2= 4х^2 - 4х^2 + 12х - 9 = 12х-9
4) (а+2b)^2 - 4b^2= a^2 + 4ab + 4b^2 - 4b^2= a^2 + 4ab
5) (x-3)^2+x(x+9)= x^2 - 6x + 9 + x^2 + 9x = 2x^2 + 3x + 9
6) 9b(b-1) - (3b+2)^2 = 9b^2 -9b - 9b^2 - 12b - 4 = -21b -4
7) (b-4)^2 +(b-1)(2-b)= b^2 - 8b + 16 + 2b - b^2 + 2b + b = 16 - 4b
8) (5+2y)(y-3)-(5-2y)^2= (5y - 15 + 2y^2 - 6y)- 25 + 20y - 4y^2 = -2y^2 + 19y - 40
2) (5х-1)^2- 25х^2= 25х^2 -10х +1 - 25х^2 = 1- 10х
3) 4х^2 - (2х-3)^2= 4х^2 - 4х^2 + 12х - 9 = 12х-9
4) (а+2b)^2 - 4b^2= a^2 + 4ab + 4b^2 - 4b^2= a^2 + 4ab
5) (x-3)^2+x(x+9)= x^2 - 6x + 9 + x^2 + 9x = 2x^2 + 3x + 9
6) 9b(b-1) - (3b+2)^2 = 9b^2 -9b - 9b^2 - 12b - 4 = -21b -4
7) (b-4)^2 +(b-1)(2-b)= b^2 - 8b + 16 + 2b - b^2 + 2b + b = 16 - 4b
8) (5+2y)(y-3)-(5-2y)^2= (5y - 15 + 2y^2 - 6y)- 25 + 20y - 4y^2 = -2y^2 + 19y - 40
Похожие вопросы
Предмет: Українська мова,
автор: maksimreminskij
Предмет: История,
автор: volodimirmorozov11
Предмет: Химия,
автор: ychenik771
Предмет: Математика,
автор: dimasharov04